Vaksininasi Protein Ekskretori-Sekretori Toxoplasma gondii Hasil Biakan in vivo Membangkitkan Respons Imun Non Protektif (THE VACCINATION OF Toxoplasma gondii EXCRETORY-EXCRETORY PROTEINS FROM IN VIVO CULTURE ENHANCED IMMUNE RESPONSE UNABLE PROTECTIVE) - ., Mufasirin; Suprihati, Endang (Jurnal Veteriner, 2013)
The aims of this research was to explore the immune response and protectiveness of mice whichwere vaccinated with Toxoplasma gondii excretory-secretory proteins produced from in vivo culture. A totalof 50  Balb/c strain mice were allotted  into five groups. Mice in group 1 to 3 were vaccinated with 20.7 kDa,35.3 kDa, and 100.9 kDa of the protein, respectively.  Whereas mice in group 4 were given total  excretory-secretory antigen ( total ESA5), and mice in group 5 were used as  control (PBS).  Booster  vaccinated wasconducted at two weeks following the first vaccination. Prior the challenge test, five mice were sacrificed forimmunologlobulin-G (IgG) analysis. The analysis of IgG using enzyme linked immunosorbent assay (ELISA).Challenge test used 1x103 T. gondii tachyzoites which were given to the animals   intraperitoneally.  Theresults showed that vaccination using  T.gondii excretory-secretory proteins as well as T. gondii total ESAscould enhanced immune response as detected by the markedly  presence of T. gondii  IgG.  However, thiswas unable to protect against T. gondii RH strain infection.
Keywords: Toxoplasma gondii RH strain, excretory-secretory antigens, 20.7 kDa, 35.3 kDa, 100.9 kDa, immune response, vaccination